PENGARUH PERGANTIAN AUDITOR, UKURAN KAP, DAN LABA RUGI TERHADAP AUDIT REPORT LAG (Studi Empiris Perusahaan Manufaktur Tercatat dalam Daftar di BEI Tahun 2016-2018) - Telaumbanua, Desta Jess Wijaya; Dwisyafitri, Jenny Indah; Sherlia, Bella; Hutabalian, Hermanto; Rahmad, Rahmad; Ginting, Wenny Anggeresia (2020)
The purpose of this study is to look at the effect of auditors, size of a public accounting firm, and profit and loss will Audit Report Lag on manufacturing companies listed on the Stock Exchange in the period 2016-2018. This type of research is qualitative research. The population is 130 manufacturing companies. In determining the sample with a purposive sampling method, the technique for determining specific evaluation examples includes: (1) manufacturing companies listed on the IDX in 2016 to 2018 are 130 companies (2) companies that do not present budget details in 2016 to 2018 are 17 companies (3) companies that have an average value below 63 and above 100 are 21 companies (4) companies that experience delays in issuing their financial statements in the end of year period rather than on December 31 are 2 companies. Based on these standard a sample of 90 companies from 130 manufacturing companies was written on the IDX in 2016-2018, so the data analyzed were 90 companies. The analysis technique is multiple linear regression. Based on the results of this study, it can be seen that (1) size of a public accounting firm has a negative and insignificant impact on audit report lag, it can be seen in the regression coefficient value (-0,227) < t table (1.66277) and it significance value is 0.821 > 0.05. (2) Change of auditor has a good and meaningless impact on audit report lag, it can be seen from the coefficient value (1,809) > t table (1,66277) and the significant value of 0.074 > 0.05. (3) Profit and loss has a good and insignificant impact on the audit report lag, it can be seen in the coefficient number (-1.760) > t table (1.66277) and a significant value of 0.082 > 0.05.